Optimalisasi keterampilan merajut sebagai solusi peningkatan ekonomi warga saat pandemi - Adi Sumarsono; Siti Nurleha; Dicha Ummi Khasanah; Novia Natasya Wardani; Wahyuni Wahyuni; Sriyani Sriyani; Dewi Listiani; Kasmawati Kasmawati (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
The pandemic of the spread of Covid 19 has an impact on all areas, one of which is the family economy. The purpose of this service includes two things, namely assisting the community to recognize and make types of skills in the form of knitting, and to produce products which are then marketed to improve the economy of the community. This service activity method is carried out in three ways, namely training, implementation and mentoring. The subjects of this service activity are members of the community, especially housewives in Rimba Jaya Village in Merauke Regency. The results of this activity include two things, first, the partner community has experienced an increase in knowledge, understanding and skills in knitting by 39.3 percent and an increase in partner skills in the form of bag knitting types, mask models, mask connector models, and hats. and songkok. Second, the products that have been produced have begun to be marketed through online media in Merauke Regency. The achievement of this service is very dependent on the consistency of the spirit of partners to work during a pandemic and becomes the second choice after activities as a farmer.